Nerve conduction study in children with thalassemia - Negi, Banita; Bhardwaj, Parveen; Sharma, Minoo; Sharma, Sudhir; Grover, Neelam (International Journal of Research in Medical Sciences, 2018)
Background: Regular blood transfusion and iron chelation therapy has increased life span of children with Thalassemia and with prolongation of life expectancy the toxic effect of iron on nervous system are being increasingly reported. Aim was to study nerve conduction study in thalassemia children and effect of iron overload on NCV. Methods: 30 children with thalassemia on regular transfusions and iron chelation therapy and 30 healthy age and sex matched controls were subjected to nerve conduction study on three motor and sensory nerves. Statistical analysis used: means of quantitative variables were calculated in two groups and compared with student t- test. A p-value of <0.05 was taken as significant. Results: On comparing the results the between cases and controls, we found that, there was no significant difference in the distal latency, amplitude and nerve conduction velocity of all three motor nerves and sensory nerves which were evaluated. Cases were further divided in to two groups depending upon serum ferritin level of < and >1000ng/ml. On comparing these two groups it was noted that distal latency was increased, nerve conduction velocity was slow in all the motor nerves (i.e. median, ulnar and tibial nerves) and sensory nerves (i.e. median, ulnar and sural nerves) in group with serum ferritin level >1000ng/ml and these findings were statistically significant. Conclusions: We concluded that in children with thalassemia on regular transfusion and Iron chelation regime, nerve conduction study is normal in comparison to normal control but with progressive increase in serum ferritin level, the latency and conduction velocity is decreased and is statistically significant.